3D Nanowire Arrayed Cu Current Collector toward Homogeneous Alloying Anode Deposition for Enhanced Sodium Storage. Issue 28 (6th June 2019) - Fan, Xiao‐Yong; Han, Jiaxing; Ding, Yuan‐Li; Deng, Ya‐Ping; Luo, Dan; Zeng, Xiangtian; Jiang, Zhen; Gou, Lei; Li, Dong‐Lin; Chen, Zhongwei
Abstract: Alloying electrodes are regarded as promising anodes for lithium/sodium storage thanks to their multielectron reaction capacity, moderate voltage plateau, and high electrical conductivity. However, huge volume change upon cycling, especially for sodium storage, usually causes the loss of electrical connection between active components and their delaminations from traditional current collectors, thus leading to rapid capacity decay. Herein, a unique 3D current collector is assembled from 1D nanowire arrays anchored on 3D porous Cu foams for constructing core‐shelled Cu@Sb nanowires as advanced sodium‐ion battery (SIB) anodes. The so‐formed hierarchical 3D anode with interconnected 3D micrometer sized pores and abundant voids between nanowires not only effectively accommodates the structural strains during repeated cycling but also ensures the structural integrity and contributes to a uniform ion/electron scattered distribution throughout the whole surface. When employed as anodes for SIBs, the obtained electrode shows a high capacity of 605.3 mAh g −1 at 330 mA g −1, and demonstrates a high capacity retention of 84.8% even at a high current density of 3300 mA g −1 . The 3D nanowire arrayed Cu current collector in this work can offer a promising strategy for designing and building advanced alloy anodes for lithium/sodium storage. Abstract : A 3D Cu current collector assembled from 1D nanowires grown on porous Cu foam is successfully constructed and employed for homogeneously depositing an alloying anode on its surface. When evaluated as an anode for sodium ion batteries, this unique 3D alloying anode shows better sodium storage properties than that of conventional Cu current collectors.